PENGARUH TEMPERATUR TINGGI SETELAH HOT ROLLER TERHADAP RHEOLOGI LUMPUR SARALINE 200 PADA BERBAGAI KOMPOSISI - Ardhy Agung; Abdul Hamid Hamid (Lembaga Penelitian Universitas Trisakti, 2015)
In the drilling process, the actual achievement of the desired final depth is always safely, quickly and without obstacles. Drilling operations are activities that can not be separated from a production well. So the purpose of drilling activities not only to drill safely and efficiently, but also keep a well to be able to produce well. The success of a work of drilling wells through various layers of rock are very dependent on its drilling program planning. Drilling mud is an important factor in the drilling. Drilling speed, efficiency, safety and cost of drilling mud is very dependent on this